Provision of personnel in the field of physical culture and sports in the context of the implementation of the «Strategy for the development of physical culture and sports in the Russian federation for the period up to 2030» - Sharonova A.V. ,; Leontyuk A.M. ,; Tsymbal E.A. ,; Kiprushina I.I. , (Theory and Practice of Physical Culture, 2025)
Objective of the study. As part of the implementation of the "Strategy for the Development of Physical Culture and Sports in the Russian Federation until 2030," this study aims to determine the current requirements imposed by employers on personnel in the field of physical culture and sports. Methods and structure of the study. To achieve this goal, regulatory documents, scientific and methodological materials, and training programs for specialists in the field of physical culture and sports related to personnel training were analyzed. In addition, a survey was conducted among employers and the data obtained was systematized about their expectations from employees working in this field. Results and conclusions. The results showed that, despite the high level of training of specialists at federal universities, there are problems associated with insufficient integration of various disciplines, limited application of knowledge in practice and weak interaction with the professional community. In conclusion, the authors propose a number of recommendations aimed at improving the quality of specialist training and, as a result, at the successful implementation of the Strategy for the Development of Physical Culture and Sports in the Russian Federation until 2030.